The Efficacy of Natural Mineral Water “Kara-Shoro” in Caries Prevention in Children - Eshiev, Abdyrakman; Akunov, Nursultan; Eshiev, Daniyar; Azimbaev, Nurlan; Kurmanbekov, Nursultan (International Journal of Child Health and Nutrition, 2026)
Background: Dental caries remains one of the most prevalent oral health issues among children and adults. This study investigates the efficacy of “Kara-Shoro” mineral water as a natural source of fluoride for caries prevention in children aged 7-15. The mineral water used in the study contains 7.83 mg/L of fluoride, along with high concentrations of bicarbonates (1,680 mg/L) and chlorides (4,541 mg/L), classifying it as a bicarbonate-chloride type mineral water. Methods: The research was conducted over three years in two villages of the Kyrgyz Republic and included educational, therapeutic, and preventive phases. In the test group, a regimen of regular “Kara-Shoro" mineral water use was implemented, both for topical application (oral rinsing) and systemic consumption. The control group followed standard caries-prevention methods, including toothbrushing without using this mineral water. Findings: Children consuming “Kara-Shoro” mineral water exhibited a significant reduction in caries intensity, as measured by the DMFT+dmft index (number of decayed, missing, and filled permanent and deciduous teeth) and the DMFT index (same metric, limited to permanent teeth), compared to the control group. By the end of the study, three years after the initiation of preventive measures, the DMFT index was 0.52±0.18 in the test group and 3.44±0.68 in the control group. The mean caries increment in the test group was 0.46 cavities, representing 16.91% of the increment observed in the control group, which reached 2.72 (p<0.001). The final reduction in caries prevalence in the test group compared to the control was 83.09%. No signs of fluorosis were observed in either group. Conclusion: As a result, the use of “Kara-Shoro" mineral water may be a promising approach to caries prevention in children, particularly in regions with low fluoride levels in drinking water. Further research is required to determine the optimal application regimen and assess long-term effects.